Les relations de frontière entre le Portugal et l’Espagne au temps de la dictature dans l’œuvre d’Álvaro Cunhal/Manuel Tiago - João Carlos Vitorino Pereira (Cahiers de Civilisation Espagnole Contemporaine)
As a man of clandestinity, Alvaro Cunhal was a tireless crosser of land and maritime frontiers. In his literary work, the transgressive crossing of frontiers, during the dictatorship and the Cold War, contributed to the heroisation of communist activists and the clandestine apparatus of the pcp. Frontier relations, notably between Spain and Portugal, were also to hold his attention in his political writing. Control over frontier space was as important for the Spanish and Portuguese dictators as it was for their opponents. The Iberian pact agreed between Salazar and Franco was aimed at reinforcing their respective regimes. However the frontier question was also of key importance after the Carnation Revolution. Cunhal was much in favour of frontier relations with the Spanish dictatorship but insisted more than ever on the necessary democratisation of Spain which would contribute to the consolidation of the young and fragile Portuguese democracy.